2018
DOI: 10.1128/jvi.02202-17
|View full text |Cite
|
Sign up to set email alerts
|

Differential Responses by Human Respiratory Epithelial Cell Lines to Respiratory Syncytial Virus Reflect Distinct Patterns of Infection Control

Abstract: Respiratory syncytial virus (RSV) infects small foci of respiratory epithelial cells via infected droplets. Infection induces expression of type I and III interferons (IFNs) and proinflammatory cytokines, the balance of which may restrict viral replication and affect disease severity. We explored this balance by infecting two respiratory epithelial cell lines with low doses of recombinant RSV expressing green fluorescent protein (rgRSV). A549 cells were highly permissive, whereas BEAS-2B cells restricted infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 67 publications
(68 reference statements)
5
52
0
1
Order By: Relevance
“…Host gene response after RV infection has been previously compared to that of influenza virus infection in a human bronchial epithelial cell line BEAS-2B cells using microarray analysis (Kim et al, 2015). However, BEAS-2B has high basal production of interferon-stimulated genes which may affect the response of other host genes (Seng et al, 2014;Hillyer et al, 2018). In this study, we compared the host response between influenza virus and RV in a well-characterized lower airway cell line, Calu-3, using RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…Host gene response after RV infection has been previously compared to that of influenza virus infection in a human bronchial epithelial cell line BEAS-2B cells using microarray analysis (Kim et al, 2015). However, BEAS-2B has high basal production of interferon-stimulated genes which may affect the response of other host genes (Seng et al, 2014;Hillyer et al, 2018). In this study, we compared the host response between influenza virus and RV in a well-characterized lower airway cell line, Calu-3, using RNA-seq.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the interferon pathway was significantly enriched in the COVID-19 cases in the NS group, which might reflect the viral responses of epithelial cells [41,42]. Enrichment of the interleukin pathway was found in the SP samples, which might indicate viral responses of immune cells [43,44].…”
Section: Accepted Manuscript Discussionmentioning
confidence: 94%
“…Transcriptomic and proteomic studies have shown the profound impact of HRSV on the physiology of respiratory epithelial cells, its main targets for infection. However, most of those studies have focused on the early innate immune response elicited in the infected cells [12][13][14]. Although, changes in other aspects of the virus-host cell interactions have also been reported, including those involving cell growth, cytoskeleton organization and mitochondrial electron transport [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%